Identifying Physical Drivers of Arctic Sea Ice Growth and Their Changing Roles in a Warming Climate - Peter Yu Feng Siew; Yutian Wu; Mingfang Ting; Cheng Zheng (Geophysical Research Letters)
Abstract Arctic sea ice extent grows from its September minimum through winter, influenced mainly by September sea ice conditions and atmospheric circulation during the ice‐growing season. However, the changing role of the two drivers in a warming climate remains unclear. Using large‐ensemble climate model simulations and Ridge Regression, this study quantifies the changing relative importance of the two drivers from 1861 to 2100. Up until recent years, low September sea ice largely enhanced sea ice growth via a negative feedback, as open water allows more freezing when the water is still cold enough. However, this negative feedback weakens with rising Arctic air and ocean temperatures that increasingly limit and delay sea ice freezing. Atmospheric circulation will relatively play an increasing role in driving sea ice growth in the next few decades. These findings are useful in guiding future studies for improving Arctic sea ice seasonal forecasts and long‐term projections.